2011
DOI: 10.1542/peds.2010-1962
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Best-Care Practices in Childhood Asthma: Quality Improvement in Community Health Centers

Abstract: On a larger scale, this approach realized impressive changes in provider clinical practice associated with major improvements in health outcomes. It holds great potential for significantly reducing asthma-related morbidity among low-income children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 43 publications
3
18
0
Order By: Relevance
“…78 This study reported a 69% reduction in ED visits and hospitalizations. However, 44% of the patient sample was lost to follow-up, and significant heterogeneity in results was seen across participating sites.…”
Section: Multicomponentmentioning
confidence: 76%
See 4 more Smart Citations
“…78 This study reported a 69% reduction in ED visits and hospitalizations. However, 44% of the patient sample was lost to follow-up, and significant heterogeneity in results was seen across participating sites.…”
Section: Multicomponentmentioning
confidence: 76%
“…75 The pre-post studies reported increases in the provision of action plans (27%-46%). [76][77][78]88 Both RCTs reported nonsignificant increases in patient education/asthma action plans (7% in 1 study; relative risk = 1.82 in the other study). 73,75 SOE: low.…”
Section: Multicomponentmentioning
confidence: 93%
See 3 more Smart Citations